Good morning to you, Valentine : poems - Hopkins, Lee Bennett; DePaola, Tomie, 1934- (New York : Harcourt Brace Jovanovich, 1976)
An anthology of twenty-three Valentine poems.
Includes index.
3.5
K-3
K-3
School Library Journal
Booklist
Keywords: Saint Valentine's Day -- Juvenile poetry; Valentine's Day -- Poetry; Saint Valentine's Day -- Poetry